Shear Behavior of Self Compacting Reactive Powder Reinforced Concrete T- beams - Aziz, Ali H.; Zghair, Luma A.; Ajeel, Awadh E. (Nahrain University College of Engineering Journal, 2016)
The present research can be divided into three categories following the respective three main objectives. The first objective is to develop a self-compacting reactive powder concrete (SCRPC).The second objective is to study the effect of steel fiber content on mechanical properties of (SCRPC). The third objective is to study the effect of steel fiber content on shear behavior of (SCRPC) RC T-beams. Therefore, five beam specimens were tested, one of which were made with (NSC) (reference beam), while, the others were constructed with (SCRPC) with different steel fiber volume fraction. Besides the beam specimens, a series of casting and testing were carried out to study the properties of (SCRPC) in fresh and hardened states. Experimental results show that the use of (SCRPC) improves the shear resistance and allowing higher forces to be carried through both, web and flange. When the steel volume fraction (Vf) changed from (0%) to (1.5%), the ultimate shear strength increased about (75%) to (91%), while, the cracking load increased about (50%) to (108%). This means the cracking and an ultimate load depends essentially on concrete strength and steel volume fraction.